Demonstration of neutron radiation-induced nucleation of supercooled water. Issue 24 (19th May 2021) - Szydagis, Matthew; Levy, Cecilia; Huang, Yujia; Kamaha, Alvine C.; Knight, Corwin C.; Rischbieter, Gregory R. C.; Wilson, Peter W.
Abstract : Beginnings of ice growth in supercooled water, where nucleation is not at a surface and is caused by neutrons. This article describes the first evidence demonstrating nucleation from a neutron source. Abstract : We present here direct evidence for neutrons causing nucleation of supercooled water. Highly purified water (20 nm filtration) is cooled to well below freezing (as low as −20 °C) with a radioactive calibration source of neutrons/gamma-rays either present or removed during each of many control cooling runs for the same volume of water. When it is primarily neutrons irradiating the sample bulk, the non-equilibrium freezing point (also known as the "supercooling point") is, on average, +0.7 °C warmer than the control equivalent, with a statistical significance of greater than 5 Sigma, with systematic uncertainty included. This effect is not observed with water in the presence of gamma-rays instead of neutrons. While these neutrons should have theoretically had sufficient energy to mount the energy barrier, corroborating our results, their raising of supercooling temperature has never been reported experimentally to the best of our knowledge. The potential to use deeply supercooled solutions, not only water, as metastable detectors for radiation and perhaps dark matter or neutrino physics presents now a new avenue for exploration.